Optimizing Mosque Management to Improve Community Quality of Life - Novita, Novita; Herianingrum, Sri; Mawardi, Imron; Faizurrahman, Umar Haidar (Universitas Negeri Malang, 2024)
his study aims to describe the strategic management and management of Jogokariyan Mosque funds to improve the quality of service and empower the surrounding community. This study used an exploratory qualitative method to draw general conclusions from field facts. The data sources in this study are residents of Jogokariyan Village as recipients of mosque services selected by purposive sampling. Data collection techniques are carried out through in-depth interviews, observations, and documentation studies. Data are analyzed using inductive techniques. Jogokariyan Mosque applies strategic management in its management to achieve effective and efficient goals. The management of Jogokariyan Mosque uses a divine or heavenly management approach that focuses not only on aspects of worship but also on the social and economic empowerment of the surrounding community. The management of Jogokariyan Mosque funds is based on the principles of sincerity, transparency, and efficiency based on Islamic law with funding sourced from donations, zakat, waqf, and independent economic businesses such as Mosque-Owned Enterprises which are managed professionally.